2017
DOI: 10.1073/pnas.1708194114
|View full text |Cite
|
Sign up to set email alerts
|

Structure insight of GSDMD reveals the basis of GSDMD autoinhibition in cell pyroptosis

Abstract: Recent findings have revealed that the protein gasdermin D (GSDMD) plays key roles in cell pyroptosis. GSDMD binds lipids and forms pore structures to induce pyroptosis upon microbial infection and associated danger signals. However, detailed structural information for GSDMD remains unknown. Here, we report the crystal structure of the C-terminal domain of human GSDMD (GSDMD-C) at 2.64-Å resolution. The first loop on GSDMD-C inserts into the N-terminal domain (GSDMD-N), which helps stabilize the conformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(140 citation statements)
references
References 32 publications
2
137
0
1
Order By: Relevance
“…In 2018, the crystal structure of the mouse GSDMA3 pore was solved (Ruan et al, 2018), providing critical insight into GSDM pore formation. Although the C-terminal domain of GSDMD, as well as the full-length GSDMA3, had previously been solved (Ding et al, 2016; Kuang et al, 2017; Liu et al, 2018) and later the full-length mouse and human GSDMD (Liu et al, 2019), this was the first crystal structure giving insights into the molecular basis of pore formation. It revealed that GSDMA forms pores consisting of 27–28 protomers with an internal diameter of ∼180 Å.…”
Section: Gasdermins the Pore-forming Effectorsmentioning
confidence: 99%
“…In 2018, the crystal structure of the mouse GSDMA3 pore was solved (Ruan et al, 2018), providing critical insight into GSDM pore formation. Although the C-terminal domain of GSDMD, as well as the full-length GSDMA3, had previously been solved (Ding et al, 2016; Kuang et al, 2017; Liu et al, 2018) and later the full-length mouse and human GSDMD (Liu et al, 2019), this was the first crystal structure giving insights into the molecular basis of pore formation. It revealed that GSDMA forms pores consisting of 27–28 protomers with an internal diameter of ∼180 Å.…”
Section: Gasdermins the Pore-forming Effectorsmentioning
confidence: 99%
“…68 Pyroptosis is a type of inflammatory cell death mediated by gasdermin D (GSDMD) processing to release N-terminal GSDMD fragment which, subsequently, contributes to pore structure formation at the plasma membrane. 69,70 This results in the release into the extracellular milieu of DAMPs such as DNA, ATP, ASC oligomers, or intracellular cytokines that further recruit immune cells and perpetuate the inflammatory response and tissue damage. 71,72 MSU crystal-induced activation of GSDMD has been recently described ( Figure 2).…”
Section: Inflammasome Activationmentioning
confidence: 99%
“…In the autoinhibited state, GSDM-CT folds back onto GSDM-NT to repress its activity. The basis for this autoinhibitory mechanism was elucidated by the X-ray crystal structures of full-length (FL) mouse GSDMA3 as well as both human and mouse GSDMD (Ding et al 2016;Kuang et al 2017;Liu et al 2018Liu et al , 2019. GSDM-NT contains both α-helices and extended β-strands, whereas GSDM-CT is almost exclusively α-helical.…”
Section: Mechanism Of Gsdm Autoinhibitionmentioning
confidence: 99%